An experimental study of unsteady vehicle aerodynamics - Martin Passmore; S. Richardson; A. Imam (2001)
The transient response of a vehicle to a wind disturbance is of importance to car drivers since low level inputs can result in poor vehicle refinement, and extreme effects can result in path deviation. This paper investigates the use of an oscillating aerofoil gust generator to simulate the transient aerodynamic effects produced on a car-type bluff body during a simplified sinusoidal side gust interaction. A simplified bluff body was exposed to a range of sinusoidal cross-wind excitations corresponding to a reduced frequency of between 0.09 and 0.71 based on the model length. Unsteady measurements of surface pressure are processed to determine the side force and yaw moment and the aerodynamic magnification (***a) is calculated by comparing the transient response with a quasi-steady prediction. The transient yaw moment response is shown to exceed the quasi-steady by as much as 30 per cent. The transient side force is generally significantly less than the quasi-steady value except at the lowest frequency tested. The change in response is attributed to changes in the strength of the front and rear pillar vortices and to changes in phase relative to the quasi-steady response.